Editorial - Goran Dahllof (IAPD and Blackwell, 2008)
You are now holding the first issue of the 18th volume of the International Journal of Paediatric Dentistry in your hand. During the last year we have successfully published our first thematic issue on child psychology and dental care, with contributions from well-known research groups in the field. A well-attended symposium organized by the editorial team was held in Hong Kong during the congress of the International Association of Paediatric Dentistry with the title ‘How to Write a Successful Paper for the International Journal of Paediatric Dentistry ’.